Specific cognitive functions and depressive symptoms as predictors of activities of daily living in older adults with heterogeneous cognitive backgrounds - de Paula, Jonas J.; Diniz, Breno S.; Bicalho, Maria A.; Albuquerque, Maicon Rodrigues; Nicolato, Rodrigo; de Moraes, Edgar N.; Romano-Silva, Marco A.; Malloy-Diniz, Leandro F. (Frontiers in Aging Neuroscience, 2015)
Cognitive functioning play an important role in the performance of activities of daily living (ADL). Although and association between this two measures are usually reported in neuropsychological studies, the results are inconsistent, especially in what aspects cognitive functioning are more or less related to each functional aspect. In addition, only a few studies investigated if depressive symptoms are associated with worse functional performance in older adults. Our objective is to investigate the role of different cognitive functions and the depressive symptoms in the performance of different groups of ADL and each activity individually. We assessed 264 older adults (96 normal aging controls, 85 patients diagnosed with mild cognitive impairment and 93 with mild probable Alzheimer’s disease dementia) with low formal education (about 4 years). We used measures of ADL with different levels of complexity: Selfcare, Instrumental-Domestic and Instrumental Complex, along with composite factors of cognitive functions and the score of the Geriatric Depression Scale. Multiple linear regression analysis showed significant predictors of Instrumental-Domestic ADL (executive functions and episodic memory) and Instrumental-Complex ADL (executive functions, episodic memory and language/semantic memory), with large effect sizes (22 and 28% of explained variance). Individual analysis of each Instrumental ADL shows a heterogeneous pattern of association with different cognitive factors and depressive symptoms, with effect sizes ranging from 22 to 38% of explained variance. Our results suggest that specific measures of ADL have different cognitive predictors and that depressive symptoms are associated with activities more dependent on social contact.